2008
DOI: 10.1017/s000711450802401x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of protein supplementation for anorexia, expression of immunity and plasma leptin concentrations in parasitized ewes of two breeds

Abstract: The periparturient relaxation of immunity (PPRI) against parasites in ewes has a nutritional basis. We investigated whether ewes experience a reduction in food intake (anorexia) during PPRI and if the magnitude of anorexia is affected by host production potential and dietary protein supplementation. We also investigated whether nematode infection is linked to plasma leptin concentrations in periparturient ewes. The experiment was a 2 £ 2 £ 2 factorial design. Two breeds of twin-bearing/lactating ewes (Greyface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 45 publications
3
26
0
1
Order By: Relevance
“…Although not significant, the penalty of parasitism (L vs H) in the BW of calves was more pronounced in C (39 kg) than in D (24 kg) calves, indicating that the impact of GIN infection on growth may have been more severe in the crossbreds than in the dairy calves. This observation is in agreement with similar studies in sheep, where genotypes selected for high productivity, were more susceptible to GIN than animals selected less intensively (Amarante et al, 2004;Zaralis et al, 2009). The mechanisms that underline these observations are still under debate; genetics differences (Rauw et al, 1998), nutritional constraints (Coop and Kyriazakis, 1999) or variation in feeding behaviour have all been thought to play a role in this.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although not significant, the penalty of parasitism (L vs H) in the BW of calves was more pronounced in C (39 kg) than in D (24 kg) calves, indicating that the impact of GIN infection on growth may have been more severe in the crossbreds than in the dairy calves. This observation is in agreement with similar studies in sheep, where genotypes selected for high productivity, were more susceptible to GIN than animals selected less intensively (Amarante et al, 2004;Zaralis et al, 2009). The mechanisms that underline these observations are still under debate; genetics differences (Rauw et al, 1998), nutritional constraints (Coop and Kyriazakis, 1999) or variation in feeding behaviour have all been thought to play a role in this.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence deriving from sheep studies has demonstrated that selecting animals for improved performance, such as increased body weight gain (BWG) and wool growth, has resulted in reduced resistance to nematodes compared to unselected genotypes (Bisset et al, 2001;Simpson et al, 2009;Zaralis et al, 2008Zaralis et al, , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Greer et al (2009) noted a 20% fall in intake but no change in leptin level in lambs infected by T. colubriformis, while calves infected with Ostertagia ostertagi (10 000 larvae/day) had lower leptin but with no change in intake or weight gain (Forbes et al, 2009). Differences in dietary energy and protein may explain some of the anomalies in these studies as protein counteracts some effects of gut parasites in sheep (Forbes et al, 2009) but Zaralis et al (2009) showed that supplementary protein did not affect leptin levels or the degree of anorexia in ewes infected with T. circumcinta.…”
Section: Leptin and Inflammation And The Immune Responsementioning
confidence: 99%
“…However, in a well-characterized endotoxin injection model of disease in sheep, there was no evidence of an increase in circulating leptin, in spite of significant reductions in feed intake (Soliman et al, 2001;Daniel et al, 2003), though tumor necrosis factor and the endotoxin receptor (CD14) were both found to be expressed in the ovine adipocyte as expected. In parasitized lambs, one study suggested that leptin might be a partial factor in reduced feed intake (Zaralis et al, 2008), though in other studies, plasma leptin concentrations were unchanged by the infection (Greer et al, 2009;Zaralis et al, 2009). However, no studies have examined the effects of disease on CSF leptin levels, which could change by altered uptake of leptin independently of changes in plasma levels.…”
Section: Leptinmentioning
confidence: 99%